2005
DOI: 10.1038/sj.sc.3101889
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic paralysis: the use of M mode ultrasound for diagnosis in adults

Abstract: Study Design: Retrospective, case series. Objectives: To evaluate the use of M mode ultrasonography in the evaluation of diaphragmatic paralysis in adults. Setting: Radiology department, Princess Alexandra Hospital, Brisbane, Australia. Methods: Ten patients who were referred for evaluation of suspected diaphragmatic paralysis were evaluated using M mode ultrasound. Results: Three of the patients who were scanned demonstrated normal diaphragmatic movement. The M mode trace demonstrated normal movement of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 8 publications
0
67
0
5
Order By: Relevance
“…Fluoroscopy, ultrasound evaluation with using motion mode [3], or brightness mode ultrasonography [4] may be used preoperatively to confirm diaphragmatic paralysis, but we prefer to use thoracic computed tomography for differential diagnosis of herniation or subphrenic tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy, ultrasound evaluation with using motion mode [3], or brightness mode ultrasonography [4] may be used preoperatively to confirm diaphragmatic paralysis, but we prefer to use thoracic computed tomography for differential diagnosis of herniation or subphrenic tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, existen reportes en la literatura sobre casos de parálisis diafragmática y aparición de componentes clínicos compatibles con bloqueo de la cadena simpática cervical, luego del bloqueo de plexo braquial por vía infraclavicular [3][4][5][6][7][8]. Diversos autores han utilizado la evaluación ultrasonográfi-ca del movimiento diafragmático como técnica simple, sensible y reproducible para el diagnóstico de la parálisis del diafragma, al compararla con técnicas como la radiografía de tórax y la fluoroscopia [7,[9][10][11][12][13].…”
Section: Introductionunclassified
“…En una serie de pacientes, la evaluación ecográfica del diafragma fue realizada en posiciones supino, semisentado y de pie, en que se comparó la medición basal de reposo (luego de espiración normal) con la medición en inspiración normal y en inspiración profunda (sniff, por su denominación en inglés) [14][15][16]. Los valores promedio de desplazamiento diafragmático en reposo y en inspiración profunda reportados en la literatura fueron 1,84 ± 0,76 y 7,88 ±del hombro, quienes aceptaron participar en el estudio y dieron su consentimiento informado por escrito.…”
Section: Introductionunclassified
“…97 In addition to the above applications, m-mode USI has been used to assess pulmonary function, specifically diaphragm excursion, motility, and paralysis. 2,32,39,78,113 Furthermore, it has been found to be beneficial in assisting and guiding treatment in those with muscular dystrophy. Researchers assessing diaphragmatic motion using m-mode USI have found that gender, body mass index, waist circumference, and age influence the amount of excursion.…”
Section: M-mode Ultrasound Imagingmentioning
confidence: 99%